A qualitative study of beach volleyball student athlete career transition at Malang State University - Irfan Panji Rifai; Kurniati Rahayuni; Yulingga Nanda Hanief; Moch Yunus (Journal of Science and Education (JSE), 2022)
This study uses case studies to determine the career transition process of student-athletes in beach volleyball at the Malang State University. The case study is a detailed description and in-depth case disclosure of a phenomenon. This case study was conducted on 2 student athletes in beach volleyball at the Malang State University who already have a minimum achievement at the provincial level. Collect data using a semi-structured interview instrument and process the data using the thematic analysis method. This research was conducted at the Faculty of Sports Science, Malang State University. The results of the research based on the data obtained, there are three themes related to this research: 1) Challenges when being a student-athlete; 2) Student athletes' barriers and 3) Athletes' thinking patterns when they become student-athletes. This article also compares previous studies related to student-athlete career transitions.